A novel mode of embryonic nutrition in the tiger shark, Galeocerdo cuvier. Issue 2 (7th February 2016) - Castro, José I.; Sato, Keiichi; Bodine, Ashby B.
ABSTRACT: How are tiger shark embryos nourished to large size without a placental connection? Tiger sharks belong to the family Carcharhinidae, and all carcharhinid sharks are placental with the exception of the tiger shark. The aim of this study was to test the hypothesis that tiger shark embryos are nourished to large size by imbibing a clear uterine fluid found in their egg cases. Based on weights of fertilized eggs and of term embryos, the tiger shark is a matrotrophic species, and its embryos appear to reach gains of 2119% in wet weight and 1092% in dry weight during gestation. By measuring the total energy content of the fluid in the egg case by chemical oxygen demand (COD), the authors demonstrate that clear liquid in the tiger shark egg case is an energy-rich embryotrophe that nourishes the embryos to large size. We suggest that the process be termed 'embryotrophy'. The process appears to be an adaptation for producing large broods of large embryos in a species lacking a placental connection.